ACTUALIZATION OF GUS DUR'S RELIGIOUS TOLERANCE AS A FORM OF IMPLEMENTATION OF MULTICULTURAL VALUES IN INDONESIA - Wawan Hermawan (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Religious tolerance is the main thing in realizing harmony between people in the life of Indonesian society which consists of various religions and cultures. Abdurrahman Wahid is a figure who provides a role model for special communities in Indonesia regarding harmony, diversity, and religious tolerance. The focus of this research is to describe the actualization of religious tolerance of Abdurrahman Wahid or Gus Dur in implementing multicultural values in Indonesia. This research is a type of qualitative research, using a narrative approach, with data validation using theoretical triangulation, the research data is interviews, data analysis techniques using interactive analysis (Milles Huberman) which include: data reduction, data presentation, and conclusions. The results of this study indicate that Abdurrahman Wahid seeks to provide an example for religious people to uphold multicultural values in people's lives in Indonesia. This is done with mutual respect and respect for each religious believer as a form of tolerance in an effort to create inter-religious harmony. The application of Abdurrahman Wahid's multicultural values in the lives of Indonesian people plays an important role in creating national unity and integrity. Not only upholding religious tolerance which is the essence of diversity, Abdurrahman Wahid also fights for the rights of religious minorities. This is done because minority religions have the same rights as the majority religions in carrying out their worship and carrying out their life activities, so Abdurrahman Wahid's goal is not to discriminate against minority religions. The application of multicultural values carried out by Abdurrahman Wahid in realizing religious harmony can actually be carried out by every religious community in social life, because Abdurrahman Wahid's sacrifice and struggle in upholding tolerance is a role model that can be emulated by every religious believer. The results of this study have implications for the life of the Indonesian people as a reflection of a harmonious life that respects differences. Not only that, the results of this study can also be used as role models for real life in people's lives who apply religious tolerance. Keywords: religion, tolerance, multicultural